Media Video Makanan Terhadap Pengetahuan Dan Kepatuhan Diet Serta Pengendalian Kadar Glukosa Darah Pasien Diabetes Melitus Tipe Ii - Nonce Nova Legi; Muksin Pasambuna; Rudolf B. Purba; Oktavia Kasiati (POLTEKKES KEMENKES MANADO, 2019)
Changes in lifestyle from year to year increasingly experiencing developments in all fields, including influencing the type of food and consumption patterns and lifestyles. The increasing number of instant foods and drinks with high calorie, low fiber and high fat content increases the risk of developing metabolic and degenerative diseases. Coupled with a lifestyle that lacks physical activity. One of the metabolic and degenerative disorders that arise is diabetes mellitus. This type of research is a quasy experiment pre and post test one group design of 34 respondents. This research will describe the increase in knowledge, diet compliance and control of blood glucose levels in patients with diabetes mellitus at RSUP Prof. Dr. R. D. Kandou Manado. Data analysis for prior and after knowledge using the Wilcoxon test and the level of dietary compliance before and after using the Paired t-test. The results showed that the knowledge of the sample after being given nutritional counseling using food videos increased by 35.3%, from 64.7% to be better, the level of adherence to the patient's diet after being given nutritional counseling using food videos increased by 2.9% from 97.1% and sugar levels blood after being given nutritional counseling using food video media decreased from 261.8 mg / dL to 195.2 md / dL